A general strategy to develop cell membrane fluorescent probes with location- and target-specific fluorogenicities: a case of a Zn2+ probe with cellular selectivity. Issue 100 (29th November 2019) - Deng, Fei; Liu, Limin; Qiao, Qinglong; Huang, Chunfang; Miao, Lu; Xu, Zhaochao
Abstract : An aggregate–disaggregate strategy to design fluorogenic probes to image Zn 2+ at the cell membrane without a wash-out procedure. Abstract : We reported fluorescent probes to image Zn 2+ with plasma membrane-specific and Zn 2+ -specific fluorogenicities. The probes contained hydrophobic alkyl chains as membrane-anchored domains and hydrophilic zinc sensor ZTRS, and aggregated to display quenched fluorescence. Cells dissolved the aggregates and the liberated probes were dispersed on the outside of the cell plasma membrane. Aggregates that did not bind to the cell membrane still exhibited aggregation-induced fluorescence quenching after complexing with zinc ions, while probes anchored on the membrane surface exhibited a fluorescence-enhanced response upon recognition of zinc ions.